Answer:
-2x-6 I think
Step-by-step explanation:
I think that it is -2x-6 because I did -2 and x is -2x and -2 times -3 is 6.
Answer:
Proof in explanation.
Step-by-step explanation:
I'm going to attempt this by squeeze theorem.
We know that
is a variable number between -1 and 1 (inclusive).
This means that
.
for all value
. So if we multiply all sides of our inequality by this, it will not effect the direction of the inequalities.
![-x^4 \le x^4 \cos(\frac{2}{x}) \le x^4](https://tex.z-dn.net/?f=-x%5E4%20%5Cle%20x%5E4%20%5Ccos%28%5Cfrac%7B2%7D%7Bx%7D%29%20%5Cle%20x%5E4)
By squeeze theorem, if ![-x^4 \le x^4 \cos(\frac{2}{x}) \le x^4](https://tex.z-dn.net/?f=-x%5E4%20%5Cle%20x%5E4%20%5Ccos%28%5Cfrac%7B2%7D%7Bx%7D%29%20%5Cle%20x%5E4)
and
, then we can also conclude that
.
So we can actually evaluate the "if" limits pretty easily since both are continuous and exist at
.
![\lim_{x \rightarrow 0}x^4=0^4=0](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Crightarrow%200%7Dx%5E4%3D0%5E4%3D0)
.
We can finally conclude that
by squeeze theorem.
Some people call this sandwich theorem.
65%...
26 divided by 40 = 0.65 x 100 = 65%
hope this helps!
Always
a=b
subtract c from each side
a-c = b-c